2010
DOI: 10.1177/0018726710375996
|View full text |Cite
|
Sign up to set email alerts
|

Discursive positioning and planned change in organizations

Abstract: This study uses discursive positioning theory to explore how planned change messages influence organizational members' identity and the way they experienced organizational change. Based on an in-depth case study of a home healthcare and hospice organization that engaged in a multiyear planned change process, our analysis suggests that workers experienced salient change messages as constituting unfavorable identities, which were associated with the experiences of violation, recitation, habituation, or reservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Poorly managed change communication can result in rumors and resistance. In a study of change messages as discursive constructions, Bisel and Barge (2011) found the formal organizationally sponsored change messages negatively influenced employee identities. Employees experienced feelings of violation, recitation, habituation, or reservation.…”
Section: Sustainability Championsmentioning
confidence: 99%
“…Poorly managed change communication can result in rumors and resistance. In a study of change messages as discursive constructions, Bisel and Barge (2011) found the formal organizationally sponsored change messages negatively influenced employee identities. Employees experienced feelings of violation, recitation, habituation, or reservation.…”
Section: Sustainability Championsmentioning
confidence: 99%
“…Yet, expectations about how work relationships will unfold (e.g., only supervisors are the source of corrective feedback) may create outcomes in which actions (e.g., withholding upward negative feedback) produce the social contexts (i.e., climates of silence) by which the certainty of the predictions are judged (e.g., ''My supervisor won't listen because that's how things work around here''). Obviously levels of hierarchy shape communication messages (Bisel & Barge, 2011).…”
Section: Hierarchiesmentioning
confidence: 99%
“…As Bisel and Barge explain, "messages do more than just simply convey information when we communicate, we position ourselves and others and call various identities and relationships into meaning." 91 Again, to answer the "what is happening here" question as evoked through the process of sensemaking, individuals are forced to inherently reference the self: the answer is always in reference to the "who am I?" question.…”
Section: Labeling and Defining Terrorism And Terrorist Organizationsmentioning
confidence: 99%